2020
DOI: 10.1021/acs.oprd.0c00294
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Perspective on Online Flow Reaction Profiling Using a Miniature Mass Spectrometer

Abstract: Online mass spectrometry has proven to be a useful tool for characterizing many aspects of chemical reactions. However, to the best of the authors' knowledge, no reference standard (RS) quantitation approach has been applied in online MS profiling work to date. In this study, we present a RS approach for online quantitation of an aerobic oxidation reaction in flow using a miniature mass spectrometer, with both internal RS and external RS quantitation approaches being evaluated. Quinoline, a structurally simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…To be robust, the coupling of a µR with an MS detector for real-time monitoring requires designing adapted set-ups allowing high adaptability (concentration level of reagents, nature of the reaction solvent, nature and number of monitored compounds…) while maintaining the performance of the mass analyzer. Different studies related to the use of MS to monitor a chemical reaction have already been published (1,3,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) (see Table S1 in supplementary materials). Most of the oldest studies involved directing the entire flow from the µR directly into the MS ionization source (1,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To be robust, the coupling of a µR with an MS detector for real-time monitoring requires designing adapted set-ups allowing high adaptability (concentration level of reagents, nature of the reaction solvent, nature and number of monitored compounds…) while maintaining the performance of the mass analyzer. Different studies related to the use of MS to monitor a chemical reaction have already been published (1,3,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) (see Table S1 in supplementary materials). Most of the oldest studies involved directing the entire flow from the µR directly into the MS ionization source (1,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies described the use of solvents, such as dichloromethane (DCM) or toluene, which are not recommended in MS as they are too volatile to be infused at 100% in the ionization source, but which were sufficient for the identification of reaction products, their quantitation of being not the objective of these studies. The introduction of a single T-piece to dilute the µR effluent with an MS-compatible solvent (10) and of a second T-piece allowing to split the effluent and then decrease the flow-rate entering the ionization source was also proposed (3,11,12,(15)(16)(17). Even if the objective was only a qualitative monitoring of the produced compounds, one of this study showed that the composition of this MS-compatible solvent (proportion of acetonitrile (ACN) in water and nature of the acid additive) strongly affects the MS signal of the monitored compounds (3).The dilution of the whole µR effluent was also achieved by digital microfluidic by merging droplets (14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, a compact LC‐UV‐MS instrument was coupled to commercial reaction vessels and larger reaction workstations, primarily focused on online process monitoring in a pharmaceutical industry setting [11]. The same compact MS has also been coupled directly to a reaction vessel for sampling, using an in‐line membrane‐based phase separator rather than a chromatographic separation [23]. In this study, an integrated compact LC platform using capillary column cartridges was implemented for online monitoring of smaller reaction volumes (on the order of 10–30 mL) with a standard syringe pump for sampling, representing a common strategy that may be used in academic and small‐scale R&D environments as an alternative to some larger‐scale automated samplers [24].…”
Section: Introductionmentioning
confidence: 99%